2021
DOI: 10.13064/ksss.2021.13.3.039
|View full text |Cite
|
Sign up to set email alerts
|

Production and perception of Korean word-initial stops from a sound change perspective

Abstract: Based on spontaneous speech data collected in 2020, this study examined the production and perception of Korean lenis, aspirated, and fortis stops. Unlike the controlled experiments of previous studies, lenis and aspirated stops of males in their 30s were not distinguished by voice onset time (VOT) in spontaneous speech. Perceptual experiments were conducted on young females, the leaders of language change. F0 was found to serve as the primary cue for the perception of lenis stops, and then VOT distinguished t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, they spent more processing time in their brains. Kim (2021) analyzed word-initial Korean stops and the following vowels, and found that VOT was almost the same in lenis and aspirated stops and was short in fortis stops, whereas f0 of the following vowels was shown in the order of lenis < fortis < aspirated stops. As discussed before, closure durations can also distinguish the laryngeal contrasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they spent more processing time in their brains. Kim (2021) analyzed word-initial Korean stops and the following vowels, and found that VOT was almost the same in lenis and aspirated stops and was short in fortis stops, whereas f0 of the following vowels was shown in the order of lenis < fortis < aspirated stops. As discussed before, closure durations can also distinguish the laryngeal contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, young generations nowadays distinguish lenis and aspirated stops using f0s of the following vowels (Kang, 2014;Silva, 2006). Kim (2021) used a spontaneous speech corpus to analyze VOTs of Korean wordinitial stops produced by Koreans in their 10s through 60s of age. He reported that the Korean speakers in their 10s through 30s produced the word-initial lenis and aspirated stops with almost the same VOTs but the word-initial fortis stops with lower VOTs.…”
Section: Introductionmentioning
confidence: 99%